Low cost eye tracking for human-machine interfacing - Lemahieu, Wounter (2012)
One of the main challenges for developers of new human-computer interfaces is to provide a more natural way of interacting with computer systems, avoiding excessive use of hand and finger movements. In this way, also a valuable alternative communication pathway is provided to people suffering from motor disabilities. This paper describes the construction of a low cost eye tracker using a fixed head setup. Therefore a webcam, laptop and an infrared lighting source were used together with a simple frame to fix the head of the user. Furthermore, detailed information on the various image processing techniques used for filtering the centre of the pupil and different methods to calculate the point of gaze are discussed. An overall accuracy of 1.5 degrees was obtained while keeping the hardware cost of the device below 100 euros.